Genetic and Haplotype Diversity Among Wild-Derived Mouse Inbred Strains - Ideraabdullah, Folami Y.; de la Casa-Esperón, Elena; Bell, Timothy A.; Detwiler, David A.; Magnuson, Terry; Sapienza, Carmen; de Villena, Fernando Pardo-Manuel (Genome Research, 2004)
With the completion of the mouse genome sequence, it is possible to define the amount, type, and organization of the genetic variation in this species. Recent reports have provided an overview of the structure of genetic variation among classical laboratory mice. On the other hand, little is known about the structure of genetic variation among wild-derived strains with the exception of the presence of higher levels of diversity. We have estimated the sequence diversity due to substitutions and insertions/deletions among 20 inbred strains of Mus musculus, chosen to enable interpretation of the molecular variation within a clear evolutionary framework. Here, we show that the level of sequence diversity present among these strains is one to two orders of magnitude higher than the level of sequence diversity observed in the human population, and only a minor fraction of the sequence differences observed is found among classical laboratory strains. Our analyses also demonstrate that deletions are significantly more frequent than insertions. We estimate that 50% of the total variation identified in M. musculus may be recovered in intrasubspecific crosses. Alleles at variants positions can be classified into 164 strain distribution patterns, a number exceeding those reported and predicted in panels of classical inbred strains. The number of strains, the analysis of multiple loci scattered across the genome, and the mosaic nature of the genome in hybrid and classical strains contribute to the observed diversity of strain distribution patterns. However, phylogenetic analyses demonstrate that ancient polymorphisms that segregate across species and subspecies play a major role in the generation of strain distribution patterns.
10.1101/gr.2519704